Research on the Internal Flow Characteristics of Pump Turbines for Smoothing the Output Fluctuation of the Wind–Photovoltaic Complementary System - Ren, Yan; Qiao, Ruoyu; Wei, Daohong; Hou, Shangchen (Frontiers in Energy Research, 2022)
Wind and photovoltaic (PV) power generation and other distributed energy sources are developing rapidly. But due to the influence of environment, climate and geographic location, the output is very unstable, which affects the power quality and power system stability. Pumped hydroelectric energy storage (PHES) system are suitable as peaking power sources for wind and photovoltaic (Wind-PV) complementary systems because of their fast start-stop and long life. In order to level the wind and PV power output and improve energy utilization. The mathematical modeling and operational characteristics of the three subsystems in Wind-Photovoltaic-PHES (Wind-PV-PHES) complementary system, are analyzed in order to improve the generation efficiency and access capacity of wind and PV power. And the peaking characteristics of PHES system are used to balance the maximum benefit and minimum output fluctuation of the Wind-PV complementary system. The stable operation of the pumped storage unit is an important guarantee for the smooth output of the Wind-PV complementary system. Three prototype operating points are selected from the net load curve and converted to obtain the relevant parameters under different openings of the pump turbine model. And the internal flow characteristics and laws of the pump turbine under different guide vane opening conditions are summarized through the analysis of the Computational Fluid Dynamics (CFD) numerical simulation post-processing results. The study shows that the output of wind and PV power generation varies with the changes of wind speed and solar radiation respectively. The output of Wind-PV complementary system still has large fluctuations, and the PHES system can effectively suppress the power fluctuation of Wind-PV complementary system and reduce the abandoned wind and light rate. CFD technology can accurately and efficiently characterize the internal flow characteristics of the pump turbine, which provides a basis for the design, optimization and transformation of the pump turbine.